2002
DOI: 10.1128/iai.70.11.6444-6447.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Selection of Mutant Cell Lines Resistant to Infection byChlamydia trachomatisandChlamydia pneumoniae

Abstract: The lytic outcome of natural infection by Chlamydia trachomatis was exploited to select CHO (Chinese hamster ovary) cells, following chemical mutagenesis, that were deficient in their ability to sustain productive chlamydial infection. Four distinct mutant cell phenotypes with defects in either attachment or postattachment mechanisms that are required for infection by C. trachomatis and Chlamydia pneumoniae were characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…This would intuitively argue that C. trachomatis and C. caviae utilize different host cell receptors for entry. This hypothesis is supported by studies with chemically mutagenized CHO cells that exhibit different susceptibilities to infection by C. trachomatis and C. pneumoniae (18). Although we did not study C. pneumoniae here, we previously reported that infection with C. pneumoniae, like that with C. caviae, failed to induce Tyr-P of the 70-kDa protein that we have now identified as ezrin.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This would intuitively argue that C. trachomatis and C. caviae utilize different host cell receptors for entry. This hypothesis is supported by studies with chemically mutagenized CHO cells that exhibit different susceptibilities to infection by C. trachomatis and C. pneumoniae (18). Although we did not study C. pneumoniae here, we previously reported that infection with C. pneumoniae, like that with C. caviae, failed to induce Tyr-P of the 70-kDa protein that we have now identified as ezrin.…”
Section: Discussionsupporting
confidence: 55%
“…These mechanistic properties are shared by most chlamydial strains (48), suggesting a shared common chlamydial ligand and host receptor interaction. Work with chemically mutagenized Chinese hamster ovary (CHO) cells has shown that EB entry is phenotypically distinguishable from attachment since it is temperature dependent and irreversible, and the ligands and/or receptors appear to differ among chlamydial strains (7,18). Numerous chlamydial ligands (40,42,47,48) and several host receptors (10,15) have been implicated in attachment, leaving the precise molecular mechanisms largely unresolved and controversial.…”
mentioning
confidence: 99%
“…The specific bacterial ligand and host receptor(s) that mediate entry are still unclear. Heparan sulfate acts as a bridging molecule for a relatively weak and reversible interaction (12,38,41,42) that is followed by a stronger, more specific binding to an unidentified secondary receptor (5,11). Internalization is accompanied by induction of a microvillus-like structure over a large portion of the host cell in a process that is dependent upon actin polymerization (3) and is mediated through Rac (4).…”
mentioning
confidence: 99%
“…Recent efforts to understand the chlamydial entry process have employed chemically mutagenized CHO cells to distinguish two distinct stages in the chlamydial entry process (9,17). The identity of the host gene mutated to block this secondary irreversible step was not determined in either study.…”
mentioning
confidence: 99%